A Wettability Metric for Characterization of Capillary Flow on Textured Superhydrophilic Surfaces - Allred, Taylor P (Langmuir : the ACS journal of surfaces and colloids, 2017)
Surface wettability is typically characterized by measuring the static contact angle of a sessile droplet placed on the surface. For extremely wetting surfaces on which liquid spontaneously spreads into a thin liquid film, the near-zero static contact angle is not amenable to measurement and does not fully describe the wetting behavior. There are unmet needs in microfluidics, boiling heat transfer enhancement, and antifogging applications for a metric to characterize highly wetting (i.e., superhydrophilic) textured surfaces based on their capillary-driven liquid pumping performance, as a supplement to the contact angle for this highly wetting regime. To describe the wetting behavior, the textured surface can be approximated as a thin porous layer through which the liquid spreads. An analytical model is developed for the volumetric flow in this layer, which reveals a single superhydrophilicity metric that captures the wetting behavior for a given liquid. A simple experimental approach is proposed to characterize this metric by measuring the volumetric liquid intake into the surface from a filled capillary tube. This approach is validated by characterizing micropillared superhydrophilic surfaces of known geometry; the predicted and measured wetting behaviors show good agreement. The metric proposed in this study offers a simple approach for accurately characterizing and differentiating highly wetting surfaces based on their liquid pumping ability